2016
DOI: 10.4103/0972-124x.176390
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin network pattern changes of platelet-rich fibrin in young versus old age group of individuals: A cell block cytology study

Abstract: Background:To evaluate variations in fibrin network patterns of the platelet-rich fibrin (PRF) in different age groups.Materials and Methods:Ninety-five patients were divided into three age groups: Group 1: (20–39 years); Group 2: (40–59 years); and Group 3: (60 years and above). PRF was prepared from blood samples of all patients and were subjected to cell block cytology method of histological analysis and slides were prepared to histologically assess the age-related changes in (i) fibrin network patterns in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 17 publications
3
33
0
2
Order By: Relevance
“…The relatively small sample size and the short-term follow-up may be not long enough to draw definitive conclusion on tooth survival. The age range of the included samples was quite broad (25–60 years), and this could have affected the present results, since some studies reported better outcomes for the use of PRF in young patients compared to elder ones [ 52 ]. A histomorphometric analysis would have been helpful to confirm the newly formed tissues but was not included in the selected studies, and indeed it is seldom feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively small sample size and the short-term follow-up may be not long enough to draw definitive conclusion on tooth survival. The age range of the included samples was quite broad (25–60 years), and this could have affected the present results, since some studies reported better outcomes for the use of PRF in young patients compared to elder ones [ 52 ]. A histomorphometric analysis would have been helpful to confirm the newly formed tissues but was not included in the selected studies, and indeed it is seldom feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we found that cytokine levels differed with age and sex. Of course, there could be genetic, hormonal, or environmental reasons for sex- and age-related differences in cytokine levels 25 28 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the centrifugation process, with characteristics as speed and g‐force, directly impacts the architecture of L‐PRF 20 . Second, the age of the patient of whom blood is taken for L‐PRF influences the fibrin network of L‐PRF 21 . These two factors must be kept in mind for in vivo applications of L‐PRF, but could not have been influencing factors in this in vitro study as all L‐PRF membranes were generated according to the same centrifugation protocol and were taken of volunteers with more or less the same age.…”
Section: Discussionmentioning
confidence: 99%